2007
DOI: 10.1007/s00442-007-0839-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance of invasive and native Celastrus species across environmental gradients

Abstract: The ability to understand and predict the success of invasive plant species in their new ranges is increased when there is a sympatric native congener available for comparison. Celastrus orbiculatus (oriental bittersweet) is a liana introduced into the United States in the mid-1800s from East Asia as an ornamental plant. Its native congener, Celastrus scandens (American bittersweet), ranges from the east coast of the United States as far west as Wyoming. In the Northeastern United States, C. orbiculatus is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 64 publications
3
65
2
Order By: Relevance
“…As a result, model predictions fit the data better than those of a climate-envelope model of colonization, and also generated emergent predictions that would not be gleaned from the simpler model alone. For example, while we found that edge habitats were optimal for the vine Celastrus orbicularis in the south (as expected from previous work; Leicht-Young et al 2007) the most suitable habitat in the north switched towards forest habitats due to their interaction with climate (see Appendix: Fig. A2).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As a result, model predictions fit the data better than those of a climate-envelope model of colonization, and also generated emergent predictions that would not be gleaned from the simpler model alone. For example, while we found that edge habitats were optimal for the vine Celastrus orbicularis in the south (as expected from previous work; Leicht-Young et al 2007) the most suitable habitat in the north switched towards forest habitats due to their interaction with climate (see Appendix: Fig. A2).…”
Section: Discussionsupporting
confidence: 85%
“…It was first planted as an ornamental species and soon after became naturalized. In its invasive range in the northeastern United States, it is commonly found in forest edges with high light levels, but can also grow under the forest canopy (Leicht-Young et al 2007). Its colorful fruits persist late into the winter, constituting a reliable source of food for wildlife, which disperse the seeds locally (Greenberg et al 2001, LaFleur et al 2007.…”
Section: Case Study 1: Oriental Bittersweet Celastrus Orbiculatusmentioning
confidence: 99%
“…Given our sample size, including more correlated predictors would have led to parameter identifiability issues. Sites within regions were chosen to characterize variation in microsite conditions, including light [from full sunlight to <1% transmission characterized by photosynthetically active radiation (PAR)] and soil nutrients (from circumneutral calcareous soils to poor acidic or sandy soils characterized by low soil pH and N) (12,41) (data collection details are in SI Appendix, section A). Plot locations included deciduous, mixed deciduous, and coniferous forests; open agricultural landscapes; open sandy disturbed soils; and forest canopy gaps.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals were transplanted to span geographic and/or environmental gradients larger than those delimited by current occurrence data. Experimental bioassays of species performance in natural environments can provide critical insights into the factors limiting current distributions and predicting further spread (11,12).Here, we present a mechanistic approach to assessing establishment risk for two invasive plants in New England (NE; in the Significance Invasive species are often expected to benefit from novel conditions encountered with global change. Our range models based on demography show that invasive Alliaria petiolata (garlic mustard) may have much lower establishment in New England under future climate, despite prolific success under current climate, whereas other invasive and native plants may expand their ranges.…”
mentioning
confidence: 99%
See 1 more Smart Citation